Anatomy of the nipple and breast ducts - Zucca-Matthes, Gustavo [UNESP]; Urban, Cícero; Vallejo, André (My University, 2016)
Over time, variations of mastectomy came up and started allowing the oncological safety and the possibility of an immediate breast reconstruction. Nipple sparing mastectomy (NSM) procedures have strongly increased in frequency and have become one of the best alternatives to treat breast cancer, also improving overall aesthetic outcomes and the achievement of contralateral breast symmetry. The nipple areola-complex (NAC) must be considered the identity of the breast concerning self-esteem of patients. This paper will remind the main anatomical topics around the nipple and breast ducts.
Keywords: Anatomy; Breast; Breast cancer; Breast conserving treatment; Mammoplasty; Mastectomy; Nipple